2002
DOI: 10.1515/epoly.2002.2.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of styrene with methyl-substituted styrenes in the presence of titanium monometallocenes

Abstract: This paper investigates the homo- and copolymerization of styrene with p-methylstyrene, m-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene and 2,4,6-trimethylstyrene using a Cp*TiCl3 (Cp: cyclopentadienyl) semimetallocene catalyst activated with methylaluminoxane. Syndiotactic homo- and copolymers were obtained only for the monosubstituted monomers. For the di- or trisubstituted monomers, reduced reactivities, stereoregularities, and degrees of polymerization were obtained with respect to the monosubsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The melting point for this polymer was very high, that is, 306 C. However, no melting peak was observable in the DSC profile of the other stereoregular polymer, that is, for poly(p-Me-St). This is in line with Table 3 F I G U R E 1 0 SEM images of polystyrene (a) and poly(p-tert-butylstyrene) (b) produced by 2/(iBu) 3 Al/Ph 3 CB(C 6 F 5 ) 4 as well as polystyrene (c), poly(p-tert-butylstyrene) (d) and poly(p-tert-butoxystyrene) (e) produced by 2/MMAO the previous studies which showed that syndiotactic poly (p-Me-St) did not show any melting transition [49,56,57] thought Tomotsu et al reported the T m value of 173 C for syndiotactic poly(p-Me-St). [46] That inconsistency can be attributed to many reasons, for example, different sample preparation or measurement conditions.…”
Section: Copolymerization Of Ethylene With Styrene Derivativesmentioning
confidence: 60%
“…The melting point for this polymer was very high, that is, 306 C. However, no melting peak was observable in the DSC profile of the other stereoregular polymer, that is, for poly(p-Me-St). This is in line with Table 3 F I G U R E 1 0 SEM images of polystyrene (a) and poly(p-tert-butylstyrene) (b) produced by 2/(iBu) 3 Al/Ph 3 CB(C 6 F 5 ) 4 as well as polystyrene (c), poly(p-tert-butylstyrene) (d) and poly(p-tert-butoxystyrene) (e) produced by 2/MMAO the previous studies which showed that syndiotactic poly (p-Me-St) did not show any melting transition [49,56,57] thought Tomotsu et al reported the T m value of 173 C for syndiotactic poly(p-Me-St). [46] That inconsistency can be attributed to many reasons, for example, different sample preparation or measurement conditions.…”
Section: Copolymerization Of Ethylene With Styrene Derivativesmentioning
confidence: 60%
“…Such copolymers of styrene and para ‐methylstyrene can be synthesized with the same transition‐metal catalysts used for syndiotactic styrene homopolymers. Instead of nonmetallocenes, such as tetrabenzyltitanium,5, 6 titanium menthoxide,7 and titanium tetraethoxide,8 being used as catalysts in combination with methylaluminoxanes (MAOs) as cocatalysts, more efficient half‐metallocenes such as η 5 ‐cyclopentadienyl titanium trichloride (CpTiCl 3 ),6, 9 η 5 ‐cyclopentadienyl titanium trifluoride (CpTiF 3 ),10 and η 5 ‐pentamethylcyclopentadienyl titanium trichloride (Cp*TiCl 3 ),11 activated by MAOs, have been used for detailed investigations. CpTiCl 3 /MAO has also been used in combination with Ph 2 Zn,12 and a living copolymerization has been performed at −25 °C with the Cp*TiMe 3 /B(C 6 F 5 ) 3 /AlOct 3 catalytic system 13…”
Section: Introductionmentioning
confidence: 99%